Responsibility Of Travel Companies For The Cancellation Of Umrah Departures Perspective Fatwa Dsn-Mui No: 83/Dsn-Mui/Vi/2012 Concerning Direct Sales Tiered Shari'ah (Plbs) Umrah Travel Services (Case Study On Umrah Travel In Medan City) - Awaliyah, Dinda; Zulham, Zulham (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Unlawful acts committed by some Umrah travel services against the postponement of the departure of pilgrims to the holy land. From this action, a formulation arises that researchers will do on how the travel accountability of Umrah travel services for the postponement of the departure schedule of pilgrims. Based on the provisions of Fatwa DSN-MUI No.83 83 / DSN-MUI / VI / 2012 concerning Syari'ah Tiered Direct Sales (PLBS) Umrah Travel Services, if the travel service provider fails to dispatch the pilgrims, then their obligation must provide compensation for the pilgrims' money is returned. This research uses empirical juridical research using a living case studies  approach.The results of the research that the researchers found that due to the failure of the departure of pilgrims due to several factors, there were changes in schedules from the government and the airline used which caused delays or changes in departure time that were not determined, then if the umrah travel service provider failed to dispatch the pilgrims the money would be refunded deducted accommodation costs and others that had been used to prepare for departure. The recommendations from researchers to travel travel should be able to give maximum responsibility for the Umrah trip that has been provided, and strive so that there is no failure to depart or delay departing for Umrah because pilgrims must experience disappointment and will reduce trust in the travel trip.